2022
DOI: 10.1039/d1tc06055d
|View full text |Cite
|
Sign up to set email alerts
|

Development of a magnetic hybrid material capable of photoinduced phase separation of iron chloride by shape memory and photolithography

Abstract: FeCl3 in the polymer matrix can be partially ordered using photolithography. Ordered FeCl3 has improved magnetic susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In other words, the magnetic nanoparticles require the development of technology to control the phase separation process during the dispersion of the nanoparticles, i.e., the magnetic properties need to be improved by clustering the nanoparticles together. Ikake et al [85] have developed a method to control the phase separation by combining the photoinduced phase transition and shape-memory processes (Figure 7). However, the sol-gel method also faced the problem that the high dispersion and random orientation of titania did not allow a sufficient magnetic susceptibility to be achieved for use as a magnetic lithography substrate.…”
Section: Creation Of Functional Hybrids In the Presence Of Ionic Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the magnetic nanoparticles require the development of technology to control the phase separation process during the dispersion of the nanoparticles, i.e., the magnetic properties need to be improved by clustering the nanoparticles together. Ikake et al [85] have developed a method to control the phase separation by combining the photoinduced phase transition and shape-memory processes (Figure 7). However, the sol-gel method also faced the problem that the high dispersion and random orientation of titania did not allow a sufficient magnetic susceptibility to be achieved for use as a magnetic lithography substrate.…”
Section: Creation Of Functional Hybrids In the Presence Of Ionic Liquidsmentioning
confidence: 99%
“…In other words, the magnetic nanoparticles require the development of technology to control the phase separation process during the dispersion of the nanoparticles, i.e., the magnetic properties need to be improved by clustering the nanoparticles together. Ikake et al [85] have developed a method to control the phase separation by combining the photoinduced phase transition and shape-memory processes (Figure 7). We found that UV irradiation of the highly dispersed magnetic ionic liquid TBP [FeCl 4 ] in a polymer matrix causes phase separation of the FeCl 3 particles, which coincidentally align along the polymer chain when the polymer chain is uniaxially stretched.…”
Section: Creation Of Functional Hybrids In the Presence Of Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…To introduce double-network polymers into a normal molding process, it is beneficial to generate cross-linking points after the molding process. The modular patterning of films using photoreactions can add cross-linking points after deposition. For example, Clet et al demonstrated a precise microscale patterning to modify the modulus of silicone elastomers . Furthermore, Sugimoto et al reported that by designing heat-cross-linking and photo-cross-linking parts, an increase in the Young’s modulus by more than 2 orders of magnitude was achieved by performing a photo-cross-linking process after a normal elastomer manufacturing heat process .…”
mentioning
confidence: 99%